Student’s Opinion towards the Leadership of Medium School Administrators in Pathum Thani and Sa Kaeo Province - Sanedee, Pongpipat; Seedee, Rattana (Journal of Faculty of Humanities and Social Sciences Thepsatri Rajabhat University, 2024)
The purposes of this study were 1. to study the opinions of students towards the leadership of medium school administrators in Pathum Thani Province and Sa Kaeo Province, and 2. to compare the opinions of students toward the leadership of medium school administrators in Pathum Thani Province and Sa Kaeo Province. The sample used in this study was 400 students studying in medium-sized educational institutions in Pathum Thani and Sa Kaeo Provinces sampling by multi-stage sampling method. The 23 item questionnaire was used as a research tool. Data were analyzed using percentage, mean, standard deviation, T-test, F-test, or One-way ANOVA. The study's findings showed that 1. the student’s opinion towards the leadership of medium school administrators in Pathum Thani and Sa Kaeo provinces showed the overall average at a high level. 2. For a comparison of student’s opinions towards the leadership of medium school administrators in Pathum Thani and Sa Kaeo provinces, it is found that 2.1 gender and factors in the difference of province affecting students’ opinions towards leadership in the pathfinding, aligning, empowering and modeling are different; 2.2 factors in the difference of status affecting the opinions of students the towards leadership in the empowering and modeling are different with statistically significant at the 0.05 level.